Epitope regions on U1 small nuclear RNA recognized by anti-U1RNA-specific autoantibodies. - Hoet, R M (1992)
Autoantibodies specifically directed to U1RNA were found in patients suffering from systemic lupus erythematosus (SLE) overlap syndromes. To obtain more insight in the mechanism responsible for this U1RNA-specific antibody formation and to use the antibodies eventually as a tool to study U1RNA-protein (U1RNP) interactions, the B cell epitopes on U1RNA were mapped. Using in vitro synthesized domains of U1RNA, the main epitope regions were found in stemloops II and IV. Furthermore, 3'-end or 5'-end truncation of both stemloop II and stemloop IV showed that the conformation of the stemloops is critical for antibody recognition. Mutant studies on both stemloops indicated that in the case of stemloop II the stem is the main antigenic region, whereas in stemloop IV, the loop (E-loop) is a main target. The results of this study support the idea that the anti-U1RNA autoantibody could be the result of a process driven by the human U1RNP complex itself (antigen-driven process).